Activation of bean (Phaseolus vulgaris) alpha-amylase inhibitor requires proteolytic processing of the proprotein. - Pueyo, J J (1993)
Seeds of the common bean (Phaseolus vulgaris) contain a plant defense protein that inhibits the alpha-amylases of mammals and insects. This alpha-amylase inhibitor (alpha AI) is synthesized as a proprotein on the endoplasmic reticulum and is proteolytically processed after arrival in the protein storage vacuoles to polypeptides of relative molecular weight (M(r)) 15,000 to 18,000. We report two types of evidence that proteolytic processing is linked to activation of the inhibitory activity. First, by surveying seed extracts of wild accessions of P. vulgaris and other species in the genus Phaseolus, we found that antibodies to alpha AI recognize large (M(r) 30,000-35,000) polypeptides as well as typical alpha AI processing products (M(r) 15,000-18,000). Alpha AI activity was found in all extracts that had the typical alpha AI processed polypeptides, but was absent from seed extracts that lacked such polypeptides. Second, we made a mutant alpha AI in which asparagine-77 is changed to aspartic acid-77. This mutation slows down the proteolytic processing of pro-alpha AI when the gene is expressed in tobacco. When pro-alpha AI was separated from mature alpha AI by gel filtration, pro-alpha AI was found not to have alpha-amylase inhibitory activity. We interpret these results to mean that formation of the active inhibitor is causally related to proteolytic processing of the proprotein. We suggest that the polypeptide cleavage removes a conformational constraint on the precursor to produce the biochemically active molecule.